Implementation of Literacy Culture as a Strategy in Improving the Public Speaking Ability of Elementary School Students - Fitrianingsih Fitrianingsih; Dewi Masitha; Abdussahid Abdussahid (JURNAL PENDIDIKAN IPS, 2025)
The implementation of literacy culture has a strategic role in developing students' public speaking skills, especially at the primary school level. This research was conducted at SDN 14 Sadia, Bima City to address the challenge of students' low courage and skills in public speaking. The literacy culture implemented at the school not only focuses on reading and writing activities, but is also directed at strengthening speaking skills, through activities such as reading aloud, group discussions, presentations and storytelling. The purpose of this study is to find out to what extent the implementation of literacy culture can significantly improve students' public speaking skills. This study used a qualitative approach with a descriptive method. Data was collected through observation, interviews with teachers and students, and documentation of literacy activities conducted at school. The results showed that there was a significant improvement in students' public speaking skills after the consistent implementation of the literacy culture strategy. Students became more confident, able to convey ideas coherently, and use the right intonation and expression when speaking in public. This success was supported by full support from teachers, parental involvement and the integration of literacy culture in various subjects. This study recommends that literacy culture should continue to be developed as an effective strategy in building students' communication competence from an early age as it has a positive impact not only on academic aspects but also on character development and 21st century skills.